Effect of Tailoring in an Internet-Based Intervention for Smoking Cessation: Randomized Controlled Trial - Wangberg, Silje C; Nilsen, Olav; Antypas, Konstantinos; Gram, Inger Torhild (JMIR Publications, 2011)
BackgroundStudies suggest that tailored materials are superior to nontailored materials in supporting health behavioral change. Several trials on tailored Internet-based interventions for smoking cessation have shown good effects. There have, however, been few attempts to isolate the effect of the tailoring component of an Internet-based intervention for smoking cessation and to compare it with the effectiveness of the other components. ObjectiveThe study aim was to isolate the effect of tailored emails in an Internet-based intervention for smoking cessation by comparing two versions of the intervention, with and without tailored content. MethodsWe conducted a two-arm, randomized controlled trial of the open and free Norwegian 12-month follow-up, fully automated Internet-based intervention for smoking cessation, slutta.no. We collected information online on demographics, smoking, self-efficacy, use of the website, and participant evaluation at enrollment and subsequently at 1, 3, and 12 months. Altogether, 2298 self-selected participants aged 16 years or older registered at the website between August 15, 2006 and December 7, 2007 and were randomly assigned to either a multicomponent, nontailored Internet-based intervention for smoking cessation (control) or a version of the same Internet-based intervention with tailored content delivered on the website and via email. ResultsOf the randomly assigned participants, 116 (of 419, response rate = 27.7%) in the intervention group and 128 (of 428, response rate = 29.9%) in the control group had participated over the 12 months and responded at the end of follow-up. The 7-day intention-to-treat abstinence rate at 1 month was 15.2% (149/982) among those receiving the tailored intervention, compared with 9.4% (94/999) among those who received the nontailored intervention (P < .001). The corresponding figures at 3 months were 13.5% (122/902) and 9.4% (84/896, P =.006) and at 12 months were 11.2% (47/419) and 11.7% (50/428, P = .91). Likewise, the intervention group had higher self-efficacy and perceived tailoring at 1 and 3 months. Self-efficacy was found to partially mediate the effect of the intervention. ConclusionTailoring an Internet-based intervention for smoking cessation seems to increase the success rates in the short term, but not in the long term.